Comparative study of neuroimaging features and clinical symptoms in patients with eclampsia - Meena, Neha; Meena, Suman; Meena, Khushbu; Verma, Savitri (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Eclampsia is a life-threatening emergency that remains a major cause for feto-maternal morbidity and mortality. The purpose of our study was to access various computed tomographic scan (CT) findings in eclampsia patients and compare neurological symptoms with radiological findings. Methods: A prospective analytical study was undertaken in department of obstetrics and gynecology, J. K. Lon hospital, Kota during the period of 2019-2020. Women who presented as eclampsia and admitted in indoor wards were included in the study. Data analyzed included various maternal and fetal parameters, CT scan findings and outcome of pregnancy. Results: The incidence of eclampsia was 1.1% of total deliveries. High risk factors associated with eclampsia were primigravida (70%), maternal age (70% in 21-25 years age group), illiteracy (64%), inadequate antenatal care (96%), early gestation (68%). On CT scan findings 52% patients had abnormal CT scan findings of which most common was cerebral edema (57.7%). Parieto-occipital lobe was most common region to be affected. Altered sensorium was found to be significantly associated with abnormal CT scan findings. Conclusions: Eclampsia is a major cause of fetal and maternal morbidity and mortality. CT scan in eclampsia have significant role in early diagnosis of patients with cerebral pathologies and these CT scan findings were associated with the level of consciousness and number of convulsive episodes. Thus, CT scan helps in further management of these patients by multidisciplinary approach.